Adapting anaerobic consortium to pure and complex lignocellulose substrates at low temperature: kinetics evaluation - Ammar Musbah Saleh Ahmed; Kovasky Alfonso Buezo; Noori M. Cata Saady (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purposes The purpose of this research was to evaluate the kinetics of anaerobic microbial culture during adaptation to pure and complex lignocellulosic substrates at low temperature. Methods Six pairs of 1.0 L batch reactors maintained at 20 °C were fed pure (xylan and cellulose) and complex (cow manure and wheat straw) lignocellulosic substrate in three successive cycles of 35 days each. The biogas volume and composition, chemical oxygen demand, and volatile solids were monitored to evaluate the kinetics of the culture during the adaption. Results Anaerobic culture adapted to digest the pure and complex lignocellulosic substrates at 20 °C in relatively short period (105 days; 3 successive cycles of 35 days each) in batch reactor studies. The first-order model kinetics revealed that the average increase (day−1 cycle−1) in the reaction rate constant over the successive cycles was 0.0831 (xylan) > 0.0235 (cow manure) > 0.0207 (wheat straw) > 0.0123 (xylan:cellulose mixture) > 0.0041 (cellulose). The rates of the substrate degradation at 20 °C were: 0.085–0.093 day−1 (cellulose), 0.112–0.278 day−1 (xylan), 0.112–0.137 day−1 (xylan:cellulose mixture), 0.069–0.116 day−1 (cow manure), and 0.057–0.106 day−1 (wheat straw). Conclusions Anaerobic mixed culture can be adapted to pure and complex lignocellulosic substrates and convert them to methane at low temperature (20 °C) in relatively short time (105 days) using a sequential procedure. The culture adaptation to wheat straw proceeded at a slower rate than that for cow manure.